Peran Guru PPKn Dalam Membentuk Karakter Disiplin Siswa Di SMK Negeri 3 Maumere - Helmina Novita Nona Noeng; Gabriel Gleko; Petrus Kpalet (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
The research aims to find out: 1) What is the role of the Civics teacher in shaping the disciplinary character education of students at SMK Negeri 3 Maumere. 2) What are the supporting and inhibiting factors for the teacher's role in shaping the disciplinary character of students at SMK Negeri 3 Maumere. This research is a qualitative research. The subjects of this study were school principals, student affairs and civic education teachers. Data collection techniques were carried out through interviews, observation and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results of the study revealed that 1) the role of the PPKn teacher in shaping the disciplinary character of students at SMK Negeri 3 Maumere through five (5) implementation of roles, namely: a) The role of the teacher as an example and example for students, b) The role of the teacher as a teacher, c) The role of the teacher as a supervisor, d) The role of the teacher as a communicator and e) The role of the teacher as an evaluator. 2) The supporting and inhibiting factors of the teacher's role in shaping the character of students at SMK Negeri 3 Maumere. In terms of supporting factors, they include a) the student's self-awareness factor, b) the teacher's collaboration factor with the student's parents, c) the school's cultural factor and d) the factor of giving reprimand efforts. While the inhibiting factors are a) the lack of self-awareness of students, b) the lack of cooperation between teachers and parents and c) environmental factors where students live.